Assessing the Reliability of Combined Scales for Spirituality Perception and Web Course Learning Adaptation among Chinese Undergraduate Nursing Students - Song, Qingqing (Journal of religion and health, 2025)
Spiritual care aims to address the requirements of the human spirit in times of trauma, disease, or grief. The purpose of this study is to examine the internal consistency and construct validity of the Spiritual Cognition Scale for Chinese context when applied with the Online Course Learning Adaptation Scale among the nursing undergraduates. A total of 228 research samples were included in this quantitative, cross-sectional study, which utilized a 1:5 standard and accounted for a 20% loss. The participants involved were nursing undergraduates with good communication, normal cognition, and willingness to participate in the study; they did not participate in other similar studies during the study period. The C-SCGS was used to assess the spiritual consciousness of nursing undergraduates. In this study, 228 questionnaires were administered, and all the administered questionnaires were retrieved hence the recovery rate was 100%. Of these, 171 were valid questionnaires, which makes the effective response rate 75%. The KMO and Bartlet tests were carried out on the data obtained from the nursing students. According to the results, the KMO value of the Chinese version of Spiritual Cognition Scale was 0. 85, and Bartlett’s sphere test was found to be statistically significant (χ2 = 1365. 23, P < 0. 001). It has been found that Cronbach’s α of the Chinese version of the Spirituality Cognition Scale was 0. 944, which means that the scale had a satisfactory level of reliability when used on nursing students. These results suggest that the C-SCGS is a reliable tool for assessing Chinese nursing undergraduate students’ attitudes toward spirituality and spiritual care.